Chinua Achebe a biography - Obaeto, Enzenwa (Bloomington Indiana University Press, 1997)
Achebe is the man who invented African literature because he was able to show, in the structure and language of Things Fall Apart, that the future of African writing did not lie in simple imitation of European forms but in the fusion of such forms with oral traditions', says Professor Simon Gikandi of the University of Michigan, Ann Arbor. This biography of Chinua Achebe captures how his personal characteristics have combined with historical events to produce the man who cleared the frontiers of literature for Africa North America: Indiana U Press; Nigeria: HEBN
Includes bibliographical references( p. 287-312 )
Keywords: Achebe, Chinua. Authors, Nigerian-20th century -Biography. Nigeria-Intellectual life